Influence of Inclusion of Fungal Treated Watermelon Straw in the Ration on Nutrient Utilisation and Rumen Fermentation in Sheep - El-Morsy, Ahmed Mahmoud (Indian Journal of Animal Nutrition, 2018)
The objective of this study was to investigate the effect of different species of fungi as biological treatments for increase improve the nutritional value of watermelon straw and on the utilization of ruminant feed. Four total mixed rations basically containing watermelon straw (WMS) treated with pleurotus columbinus, Aspergillus niger and penicillium oxalicum or untreated, were formed to study. Digestibility and nitrogen balance experiments were performed using twelve adult crossbred male sheep. Three Barki female sheep fitted with permanent rumen fistula were used to estimate rumen fermentation and fiber fraction degradation in rumen. Results of digestibility trail showed that a significantly increase (P< 0.05) in digestibility of DM, OM, CF and CP for rations treated with fungi than untreated. Also, the nutritive value TDN and DCP were higher (P< 0.05) for fungal treated rations than untreated. However, the results of rumen fermentation for pH values and ammonia nitrogen concentration indicated that no significant differences between experimental rations while, the values of rumen ammonia nitrogen concentration were ranged (13.87) to (14.50). On the other hand, the results of total volatile fatty acids concentrations and microbial protein synthesis recorded significantly increased (P< 0.05) for sheep feed fungal treated rations than those feed untreated. Furthermore, fungal treatment showed a positive effect on the degradation of the fiber fraction either cellulose or hemicellulose. WMS treated with penicillium oxalicum and pleurotus columbinus had the highest cellulose degradability (49.63) and (48.34), respectively. While, the ability of Aspergillus niger was higher for hemicellulose degradable.